Measuring Bank Efficiency and Productivity Using DEA and Malmquist Index: A Case Study of NTB Syariah Bank’s Pre- and Post-Conversion Performance - Sunardi, Sunardi; Salahuddin, Muh.; Jayadi, Edi Muhamad (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the performance of Bank NTB Syariah by measuring efficiency and productivity before and after conversion. Methodology: This study uses a quantitative method with a non-parametric approach. The data analysis technique to measure efficiency uses data envelopment analysis (DEA) with MAXDEA software. The data analysis technique to measure productivity uses the Malmquist productivity index (MPI) with DEAP software. Results: The level of productivity of Bank NTB Syariah before the conversion experienced a decrease in productivity, while after the conversion, there was an increase in productivity. Findings: The factor that plays the most role in changes in the productivity of Bank NTB Syariah is the technological change factor (TECHCH). Novelty: The measurement results based on the Malmquist productivity index show that Bank NTB Syariah's productivity levels before and after conversion were different. Before the conversion, productivity decreased, while after the conversion, it increased. The measurement results based on data envelopment analysis show that Bank NTB Syariah's efficiency levels are classified as efficient before and after the conversion. Originality: This study analyzes the productivity and efficiency of Islamic banks before and after the conversion. Conclusion: Bank NTB Syariah must continue to develop and adopt various technologies in order to continue to increase productivity. Type of Paper: Empirical research paper.